Researching the Possibility of Recycling and Reusing the Asphalt Scraper in the Layers of Asphalt Covering - سلطان بسام; جندي علا (Latakia University Journal -Engineering Sciences Series, 2021)
Research goal is to study the possibility of recycling the Reclaimed Asphalt , and reusing it in the Bituminous cover layers, Spotlight on rapid reuse or recycling technology Focusing on hot reuse as it is most suitable for the road network in Syria and Explanation of the method of asphalt institute in the design of Reclaimed Asphalt mixtures in detail. The experimental program (practical section) for this research includes the manufacture of traditional bituminous mixtures and mixtures containing Reclaimed Asphalt , Preparing samples of conventional bituminous mixtures and mixtures containing Reclaimed Asphalt in different weight proportions for Reclaimed Asphalt (10-20-30%)from total mixture, depending on the Marshall method for designing bituminous mixtures. Through experiments on mixtures, it was found that the stability values increased in mixtures containing Reclaimed Asphalt than in conventional mixtures, in mixtures containing Reclaimed Asphalt by 10% and the stability value was (2499.09 Kg). While a significant decrease in the flow value was observed in mixtures containing Reclaimed Asphalt than in conventional mixtures at the ideal bitumen ratio, the lowest stability value was recorded at (30%) of the Reclaimed Asphalt to reach (3 mm).